Prognostic significance of FSCN family in multiple myeloma - Deng, Cong (J Cancer, 2021)
Multiple myeloma (MM) is a hematologic tumor with monoclonal proliferation of malignant plasma cells in the bone marrow. Fascin (FSCN) is an actin-binding protein that plays a crucial role in cell migration and invasion, contributing to tumor metastasis. There are three members (FSCN1-3) in FSCN family. However, the prognostic role of FSCN family in MM remains unclear. In this study, we used four independent Gene Expression Omnibus (GEO) datasets to explore the relationships between FSCN1-3 expression profiles and patient survival in MM. We found that FSCN1 was dramatically down-regulated in MM compared to normal donors (p < 0.001) and monoclonal gammopathy of undetermined significance (MGUS) (p = 0.032). Patients with high expression of FSCN1 and FSCN2 had significantly longer OS (p = 0.023 and 0.028, respectively). Univariate and multivariate analysis showed that FSCN1 (p = 0.003, 0.002) and FSCN2 (p = 0.018, 0.013) were independent favorable prognostic factors for OS in MM. Moreover, the combination of high expression of FSCN1 and FSCN2 could effectively predict both longer EFS (p = 0.046) and OS (p = 0.015). Our study suggested that FSCN1 and FSCN2 can be used as favorable biomarkers for predicting clinical outcomes in MM.